Ice and Snow Thickness Variability and Change in the High Arctic Ocean Observed by In Situ Measurements. Issue 20 (25th October 2017) - Haas, Christian; Beckers, Justin; King, Josh; Silis, Arvids; Stroeve, Julienne; Wilkinson, Jeremy; Notenboom, Bernice; Schweiger, Axel; Hendricks, Stefan
Abstract: In April 2017, we collected unique, extensive in situ data of sea ice and snow thickness. At 10 sampling sites, located under a CryoSat‐2 overpass, between Ellesmere Island and 87.1°N mean and modal total ice thicknesses ranged between 2 to 3.4 m and 1.8 to 2.9 m, respectively. Coincident snow thicknesses ranged between 0.3 to 0.47 m (mean) and 0.1 to 0.5 m (mode). The profile spanned the complete multiyear ice zone in the Lincoln Sea, into the first‐year ice zone farther north. Complementary snow thickness measurements near the North Pole showed a mean thickness of 0.31 m. Compared with scarce measurements from other years, multiyear ice was up to 0.75 m thinner than in 2004, but not significantly different from 2011 and 2014. We found excellent agreement with a commonly used snow climatology and with published long‐term ice thinning rates. There was reasonable agreement with CryoSat‐2 thickness retrievals. Key Points: Snow and ice thickness and northern extent of multiyear ice were observed in April 2017 with unique in situ measurements Modal, total ice thickness ranged between 1.8 and 3.2 m, little different from 2011 and 2014, but 0.75 m thinner than in 2004, and consistent with thinning rates over 2000–2012 Mean and modal snow thicknesses varied strongly between 0.3 to 0.47 m and 0.1 to 0.5 m, respectively, in close agreement with climatology